Utilization of educational applications in assessing the reading skills of junior high school students - Didin Nuruddin Hidayat; Yatni Fatwa Mulyati; Nida Husna (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Utilization of educational applications in assessing the reading skills of junior high school studentsGlobalization and the advancement of technology are giving a new challenge as well as opportunities for English educators around the globe. Indirectly, there are obstacles associated with learning English due to the fact that technology has become an integral aspect of human existence. The teaching of reading skill also faces the same challenge. Nowadays, reading is seen as more important than other skills, considering that reading has become one of the aspects of literacy. With regard to assessment, the availability of an educational application might be advantageous for teachers to assess students' reading skills. The current study investigates the types of application used by teachers in assessing students’ reading skill and the type of reading assessment that occur during the implementation of the application. Through open-ended interview and document analysis method, the research result indicates that the implementation of Google Form as an educational application to assess students reading skills demonstrated a reading assessment based on traditional assessment approaches with a focus on intensive reading. This study has shown the appropriate media for assessing students reading skill along with the reading focuses and assessment design that is suitable for it. In addition, in this study, Google Form dominates the most considerable use of media to assess students reading skills. Therefore, teachers could also save more time in assessing students’ reading by utilizing educational applications.Penggunaan aplikasi pendidikan dalam menilai ketrampilan membaca siswa SMPGlobalisasi dan kemajuan teknologi memberikan tantangan sekaligus peluang baru bagi pengajar bahasa Inggris di seluruh belahan dunia. Secara tidak langsung, terdapat kendala yang terkait dengan pembelajaran bahasa Inggris karena fakta bahwa teknologi telah menjadi aspek yang tidak terpisahkan dari keberadaan manusia. Saat ini, membaca dipandang lebih penting daripada keterampilan lainnya, mengingat membaca telah menjadi salah satu aspek literasi. Secara khusus, menentukan keterampilan membaca siswa menjadi sangat penting dalam pengajaran dan penilaian bahasa, dengan penambahan aplikasi pendidikan yang mungkin bermanfaat bagi guru untuk menilai keterampilan membaca siswa. Penelitian ini bertujuan mengidentifikasi aplikasi pendidikan yang dimanfaatkan untuk menilai ketrampilan membaca dan jenis-jenis ketrampilan membaca yang dinilai menggunakan aplikasi. Melalui metode wawancara terbuka dan analisis dokumen, hasil penelitian menunjukkan bahwa implementasi Google Form sebagai aplikasi pendidikan untuk menilai keterampilan membaca siswa menunjukkan penilaian membaca berdasarkan pendekatan penilaian tradisional dengan fokus pada membaca intensif. Penelitian ini telah menunjukkan media yang sesuai untuk menilai keterampilan membaca siswa beserta fokus membaca dan desain penilaian yang sesuai dengannya. Selain itu, dalam penelitian ini, Google Form mendominasi penggunaan media yang paling banyak digunakan untuk menilai kemampuan membaca siswa. Oleh karena itu, guru juga dapat menghemat lebih banyak waktu saat melakukan penilaian keterampilan membaca siswa.